Effects of fretting wear process on fatigue crack propagation and life assessment. (April 2021) - Pinto, A.L.; Araújo, J.A.; Talemi, R.
Abstract: This paper proposes a new methodology for fretting fatigue life assessment. It uses a combination of multiaxial fatigue criteria, the theory of critical distances and a node-displacement wear algorithm to account for the initiation life under fretting. Further, the extended finite element method is considered to compute the propagation life. A new method is also introduced to predict the crack propagation path under nonproportional loading conditions. To validate the analysis, available fretting fatigue data using an Al 2024-T3 alloy was considered. All the total lives estimated by the proposed approach fell within a scatter band 2, with an error between 11% and −39%. An analysis of the energy dissipated on the contact surface was performed and showed that for certain cases the inclusion of wear in the modeling of the problem is indeed essential to obtain more accurate fretting fatigue life assessments. Highlights: Fretting fatigue in partial slip regime life assessment is carried out for Al2024-T3. The numerical method proposed including wear effects and crack propagation life. A new method based on the critical plane to predict the crack propagation angle. The methodology proposed obtained more accurate predictions than simple methods. The maximum energy dissipated has shown to be a parameter capable to identify when is necessary to compute wear or not.